KWH METER DIGITAL DENGAN SISTEM PRABAYAR BERBASIS IC BL0932 DAN MIKROKONTROLER 38024 - Lukito, Bimo Kristianto; Winarno, Heru (Vocational School Diponegoro University, 2013)
Bimo Kristianto Lukito, Heru Winarno, in paper prepaid digital KWH meter based on IC BL0932 and microcontroller 38024 explain that an analog meter kWh used by PLN placed in homes. Has several drawbacks, including the effects of age and weather making its numbers less opaque and can be seen. Read error resulted in the use of electrical power and recording electricity bills electricity that could harm users. To overcome these problems made ​​a digital kWh meter with prepaid systems, with the advantages of digital display are lit and large enough. The system replaced the way payments are prepaid, by using an electronic prepaid card replacement bills. Digital kWh meter is controlled by a microcontroller with type 38024 and type IC BL0932 uses a function to read the voltage and current (with load reaches 1300 watts) to determine the energy used in home installations using the LCD as a data viewer that the amount of electrical energy used at home . The payment system by purchasing an electronic voucher, containing a digital scale (functioning as a pulse) as a comparison of the amount of energy used. This system automatically decides if the magnitude of the voltage reaches a value of 0. Keywords : digital kWh meter, IC BL0932, microcontroller 38024